Feasibility and efficacy of a remotely delivered fall prevention exercise program for community-dwelling older adults with cancer: Protocol for the STABLE trial. Issue 8 (November 2022) - Sattar, Schroder; Haase, Kristen R.; Alibhai, Shabbir M.H.; Penz, Kelly; Szafron, Michael; Harenberg, Sebastian; Amir, Eitan; Kuster, Shawn; Pitters, Eric; Campbell, Diane; McNeely, Margaret L.
Abstract: Falls are a major issue in older adults with cancer due to the effects of cancer and its treatments. Ample evidence in the general population of older adults has demonstrated the effectiveness of strength and balance training in reducing fall rates in older adults. However, data on effective fall prevention interventions in the oncology setting are lacking. The objective of this study is to evaluate the feasibility and efficacy of a remotely delivered, partially-supervised, resistance and balance training program on lower body strength, balance, and falls in community-dwelling older adults with cancer. The proposed study is an observer-blinded, parallel group (intervention group vs. control group) randomized controlled trial (ClinicalTrials.gov Identifier: NCT04518098 ). This study will recruit 74 eligible community-dwelling older adults with cancer from a comprehensive cancer centre. Intervention includes a remotely delivered exercise program for 3 months. Outcome measures include feasibility measures, lower body strength, balance, and fall rates. Research ethics approval has been granted by the Biomedical Research Ethics Boards of the University of Saskatchewan. If found effective, findings from this study will inform a subsequent, phase III definitive trial, with the ultimate goal to reduce falls and reduce impact on cancer treatment. Study findings will be disseminated through presentation at community level and scientific conferences, and in scientific journals. Trial registration : ClinicalTrials.gov identifier: NCT04518098